RED BEETROOT EXTRACT ACCELERATES RECOVERY OF NONLINEAR DYNAMICS OF HEART RATE VARIABILITY FOLLOWING EXERCISE: A RANDOMIZED TRIAL - Benjamim, Cicero Jonas R. [UNESP] (2023)
Introduction: Studying the behavior on nonlinear HRV indexes in situations mediated by exercise may reveal other ways to analyze HRV recovery after stress situations. To investigate the acute effects of beet extract on autonomic recovery following an acute resistance exercise session. Methods: This is a randomized, crossover, double-blind and placebo-controlled trial. We assessed 12 healthy male adults who participated in two protocols in randomized days: Beetroot extract (600mg in capsule) and Placebo (600mg in capsule). Both protocols were applied 120 minutes prior to an exercise resistance session (75% 1RM). Nonlinear dynamics of HRV (Symbolic analysis, SampEn, DFA and HR fragmentation) were studied before, during exercise and during recovery from strength exercise. Results: Beetroot extract protocol intensified the recovery of the symbolic analysis of HRV via index 0V% (zero opposite variations) and 2UV% (two unlike variations); accelerating the recovery of fractal analysis (DFA); nevertheless, it was unable to trigger changes during recovery in SampEn and HR fragmentation. Conclusion: Ingestion of beetroot extract prior to resistance exercise improves nonlinear HRV dynamical autonomic recovery following physical effort.